The Impact of Work-Related Stress on Employees’ Performance: An Insight from the Malaysian Banking Sector - Romaiha, Noor Rafhati; Ali Mastor, Normasiah; Iskandar, Ainaa Idayu; Alias, Nurul Ezaili; Krishnan, Ramesh; Sauid, Muna Kameelah (Information Management and Business Review, 2024)
Work-related stress is inevitable especially in the service industry given the operational responsibilities and the nature of their work activities. This study examines the factors of work-related stress on employees’ performance where the three components tested are work overload, role conflict, and monetary rewards. The survey was carried out from a sample of 70 employees from a banking company in Malaysia by using structured questionnaires and other secondary sources. The collected data was then empirically analyzed by using the Statistical Package for the Social Sciences (SPSS) software version 23. The findings revealed that work overload and monetary rewards, two of the three predictive variables, have a significant impact on an employee’s performance. These findings were consistent with earlier studies conducted by several other scholars. Future research should consider including other predictors and investigating them in various industries or sectors.